Key strategies to enhance success in return to work case management - Gribble, Nigel; North, T. (Safety and Rehabilitation Books, 2016)
A successful case manager needs to draw on an array of proactive tools and strategies to assist an injured to return to work in a safe and timely manner. This chapter will outline key strategies that proactive, intuitive case managers implement to enhance the successful return to work for the injured worker. Throughout a return to work program, successful case managers are cognisant of all the factors that may impact the return to work of the injured worker including the worker’s background and social situation, as well as the range of factors in the present that may at some point impact the return to work program. As early as possible, successful case manager’s ensure key stakeholders understand their role, responsibilities and obligations in supporting the injured worker. The critical importance of the early identification of a realistic return to work goal and suitable duties cannot be underestimated. At the heart of any successful case manager is advanced communication skills whereby regular, clear and honest communication is maintained between all key stakeholders.